Product Innovation, Price Level And Competitive Advantage: A Perception Assessment Of Beer Products - Emenike O., Kalu; Olutayo, Osunsan; Moses, Agaba (Universitas Merdeka Melang, 2022)
This study evaluates the effect of product innovation and prices on competitive advantage of beer products in Kabale Uganda, by analyzing responses obtained through questionnaires using multiple regression analysis. From analysis of respondents, the percentage of targeted respondents that actually responded to the questionnaire was 96%. From the preliminary analysis conducted in this study, majority of respondents have the following attributes,1 ) diploma level education, 2) are males, 3) aged between 36-45 years, and 4) prefer Nile lager beer. The data approximates normal distribution, with absence of multicollinearity. The results of the multiple regression analysis indicate that product innovation and prices have significant effect on competitive advantage among beer products and producers in Kabale Uganda. We therefore conclude that innovation and prices have positive and significant predictive effect on competitive advantage. Hence, the firms could enhance competitive advantage by paying attention to innovation and prices variables. We therefore recommend, amongst others, that that brand managers should prioritize innovation and prices as strategies to attract and sustain competitive advantage.